Konsep Perlindungan Hukum Bagi Anak Turut Serta Dalam Melakukan Tindak Pidana Berdasarkan Hukum Positif Indonesia - Haryanto, Imam; Wahdah, Azzhara Nikita; Almagfira, Anisa; Amelia, Dean Putri; Mulya, Ilham Indra; Tambunan, Joy Catherine Carina (Media Hukum Indonesia (MHI), 2024)
Children are precious assets for the future of the nation, so legal protection for them is a crucial aspect in realizing a just and prosperous society. In Indonesia, child protection is regulated in various laws, including for children involved in criminal acts. The involvement of children in criminal acts raises concerns because they are still in the developmental stage and are vulnerable to negative environmental influences. Therefore, the authors will examine the concept of legal protection for children who participate in committing criminal acts based on Indonesian positive law. The research employs a normative juridical method, which relies on legal norms as a foundation for examining and analyzing prevailing legal regulations. Its objective is to explore and investigate a type of safeguard for minors engaged in criminal activities within the framework of Indonesian positive law, and to probe into the factors hindering the provision of legal aid to children involved in such criminal activities. The findings reveal that despite existing regulations governing legal protection for juveniles in the justice system, their execution has been suboptimal due to insufficient facilities, awareness, and funding.